Paranasal sinus dysbarism: an unrecognized entity - Vadivu, Senthil; Madhav, Koka; K., Sreenivas Kamath; Krishnan P., Vijaya; K., Karthikeyan; Kameswaran, Mohan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Sinonasal barotrauma is due to sudden change of surrounding pressure. Divers and aviators are the two main groups that get affected. Many otorhinolaryngologists are not familiar with this entity. We present a case series of five patients, in which three patients had sinus barotrauma due to flight journey and one after scuba diving and other one working in hyperbaric oxygen chamber. All five patients presented with dragging frontal headache, nasal discharge with altered blood, nasal block and were managed conservatively.